Perkembangan Obyek Wisata Benteng Marlborough Tahun 2013-2019 - Febridho Jaya Kusuma; Syarifuddin Syarifuddin; Alian (Jurnal Pendidikan Sejarah, 2022)
Marlborough at first the establishment was a fortress used as a defense place and save the results of spices. Fortress Marlborough was founded by a general named Josep Callet in 1712. In the development of the Fort Marlborough was made by the Indonesian police as headquarters and had been used as a place where the Army in 1980 Marlborough fortress was taken by the Ministry of Education and Culture to be processed into a cultural heritage. In 2004 the tourism object of the Fortress Marlborough was designated as a cultural heritage based on SK: KM.10 / PW.007 / MKP / 2004. In the present the Fort Marlborough is the purpose of historical attractions in the city of Bengkulu. The visit of the Fortress of Marlborough in 2013-2019 tends to be fluactive where it is up and down in its visit. Visitors are dominated by students and general with the age of children to adulthood. For facilities in the tourist attraction of Marlborough fortress there is an exhibition room and a library used by visitors to find out the history of the Fortress of Marlborough.